The Influence of Organizational Culture and Employee Training on Employee Performance at PT Len Industri (Persero) - Viya Ermaulandari; Dian Indiyati (Cita konsultindo, 2024)
PT Len Industri (Persero) is a state-owned enterprise focusing on the electronics sector for industry and infrastructure. Internal data from PT Len Industri (Persero) indicates a decline in employee performance from 2019 to 2022. The purpose of this study is to provide an overview of organizational culture, training, and employee performance at PT Len, as well as to determine whether there is a partial and simultaneous influence of organizational culture and training on employee performance at PT Len Industri (Persero). The method used in this research is quantitative. Data collection was done through the distribution of questionnaires to 110 employees. Data analysis techniques in this research use descriptive analysis and path analysis with the support of IBM SPSS version 27 software. The research results indicate a significant simultaneous and partial influence of each variable such as organizational culture and training on employee performance. The influence of training on employee performance at PT Len is 68.6%, while organizational culture significantly influences performance by 21.7%. Simultaneously, the influence of organizational culture and training on employee performance is 78.9%. A recommendation from the researcher is for the company to pay special attention to aspects that support organizational culture and employee training to improve employee performance within the company